Análise da desertificação nos sertões dos Inhamuns – Ceará, no contexto das políticas públicas e o papel da mídia - Oliveira, Zacharias Bezerra de (2008)
The desertification is a phenomenon that occurs in arid zones, semi-arid and subhumid droughts, caused by climatic effects and intensified by the action of the human kind, due to social, cultural and economic factors, and its consequences are ground losses and disappearance of biodiversity. The anthropic action is responsible for the intensification of the environmental degradation in as much as in developed countries as it is in developing ones. The impact of human activities on the natural environment, object of study of the natural sciences, which seek solutions to problems such as air and water pollution, deforestation, soil erosion, loss of biodiversity and desertification, affects the ecological balance of the Planet. The research “Analysis of desertification in the hinterlands of Inhamuns – Ceará, in the context of public policies and the role of the media” has its convergence area on Tauá, council approved by UNICEF for its actions in favor of the environment. The historic-geographical and scientific-cultural contextualization of the socio-environmental policies, the approach of the problem in history, music and literature and in the news of the daily papers O Povo and Diário do Nordeste, between 1992 and 2002, the evaluation of the level of information the population of Tauá, and the commitment and knowledge of journalists about the theme are some prospects proposed for this work. The desertification is an obstacle to a normal life in the hinterlands, where the casual public policies, promised by the politicians during the political campaigns and announced by the media, never arrive or accomplish, is also a menace to the socio-economical development of the State. Hence, a process of a systematic general education and of human ecology, at all levels, is the way to change this menace and the standard of poverty and distress of the semi-arid population. Moreover, it is necessary to improve the training of journalists for the coverage of environmental issues, and to change it from factual issues to monitoring of the process. It is also recommended that the State Government increments the public policies for the coexistence with the semi-arid, such as the use of the forces of the nature for the production of wind and solar energy, construction of a greater number of tanks to restore the water during the period of rain, the use of the seed oleífera for cleaning and conservation of water and construction of micro dumps with stones, systemic approach and new paradigm for agricultural production in the dry tropics, which helps conserve the soil and restore the environment.